External regenerating unit of particle trap blowback pipe - TANG YUAN; KANG WENJIE; FU JUN; LI JIANXING; YAN FEIBIN; ZHANG ZENGFENG (2015)
The utility model discloses an external regenerating unit of particle trap blowback pipe, it discharges and the pollution control field to belong to the engine, external shell and blowback gas flow tube are personally experienced sth. Part of the body, are filtered to concrete the filtration including two, blowback gas flow tube filters body exhaust end intercommunication to an exhaust end that filters the body with another, and adoption intersection control strategy, pass through the tail gas inflow pipe with partly engine exhaust and introduce one of them filtration body, another part tail gas is introduced another tail end that filters the body through blowback gas flow tube and is carried out blowback regeneration, two are filtered the body work and regeneration in turn, corresponding control flap is installed respectively to end at blowback gas flow tube and tail gas inflow pipe, open to close to open with the tail gas inflow pipe and close through alternately controlling blowback gas flow tube, thereby realize utilizing the automatic blowback of engine exhaust to filter the body, and reach and filter the body entrapment particle and palingenetic purpose in turn.